O16.5 Targeting complement receptor 3 on primary human cervical cells has the potential to cure neisseria gonorrhoeae infection. (14th July 2019) - Edwards, Jennifer; Day, Christopher; Jennings, Michael
Abstract : Background: Complement receptor 3 (CR3) is a leukocytic, pattern recognition receptor that plays a pivotal role in innate immunity. CR3 is also uniquely expressed by human cervical epithelial cells where it is the key receptor mediating Neisseria gonorrhoeae ( Ng ) cervicitis. Binding of the Ng surface appendage, pilus, to the I-domain region of CR3 (CR3ID) is critical to cervical cell adherence and modulates the host response to infection. Thus, the pilus-CR3ID interaction may pose a novel target for critically-needed, new strategies to treat or prevent Ng disease in women. Methods: To identify potential inhibitors of the Ng -CR3 interaction, recombinant human I-domain or purified CR3 were immobilized on biosensor chips. Interactions between these immobilized proteins and a library of 3141 drugs were investigated by surface plasmon resonance (SPR). Drugs that bound the CR3ID were further examined by competitive SPR studies and in Ng, primary human cervical epithelial (Pex) cell infection assays. Results: Using SPR, we identified fourteen drugs that bound to the CR3ID with disassociation constants in the nanomolar range. Competitive SPR analysis demonstrated that six of these fourteen drugs blocked the pilus-CR3ID interaction. Moreover, these drugs also blocked Ng adherence to Pex cells as well as to Chinese hamster ovary cells expressing CR3 (CHO-CR3). One drug, carbamazepine, was chosen for further analysis using a panel of low-passage and multidrug-resistant Ng strains. Carbamazepine blocked adherence to Pex and CHO-CR3 cells for all strains tested and also could cure Pex cells that had an established Ng infection. In this regard, a single dose of carbamazepine was effective in curing (≥99% Ng killing by 24h post-treatment) Pex cells infected with multidrug-resistant Ng strains, including the ceftriaxone-resistant strains WHO-X (H041) and WHO-Y (F89). Conclusion: Our data identify safe, repurposed, drugs that may have efficacy in preventing and treating Ng cervical infection in women. Disclosure: No significant relationships.